Benylin dependence, metabolic acidosis and hyperglycaemia. Issue 741 (July 1987) - MacRury, S.; Neilson, R.; Goodwin, K.
Abstract : We describe a patient who had consumed large quantities of a proprietary cough mixture containing diphenhydramine, ammonium chloride and sodium citrate (Benylin expectorant) daily for several months and subsequently presented with confusion, marked metabolic acidosis and non-ketotic hyperglycaemia.